2010
DOI: 10.1063/1.3435485
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced degradation of high performance deep ultraviolet light emitting diodes

Abstract: Lifetime measurements on single-chip, packaged 285 nm light-emitting diodes (LEDs) performed under constant current injection at 20 and 75 mA, were compared to the performance of unbiased LEDs baked at the equivalent operating junction temperatures. The thermally stressed devices showed a lesser degradation than those electrically stressed, indicating that elevated temperature alone does not cause degradation. Despite a decay to less than half of the initial power under current injection, time-resolved photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 15 publications
0
38
0
4
Order By: Relevance
“…Gradual degradation reported in Refs. [382][383][384] was not related to increased nonradiative recombination in the MQW region, but rather ascribed to generation of defects in the AlGaN cladding layers. The effect was variously explained by migration of Al in the p-AlGaN cladding layer or to enhanced compensation of p-type conductivity in this layer.…”
Section: V2leds Degradation Studiesmentioning
confidence: 87%
“…Gradual degradation reported in Refs. [382][383][384] was not related to increased nonradiative recombination in the MQW region, but rather ascribed to generation of defects in the AlGaN cladding layers. The effect was variously explained by migration of Al in the p-AlGaN cladding layer or to enhanced compensation of p-type conductivity in this layer.…”
Section: V2leds Degradation Studiesmentioning
confidence: 87%
“…So far, aging of LEDs with emission wavelength as short as 280 nm has been studied by measuring electrical, far field optical, and noise properties. 2,3,[5][6][7] Aging mechanisms, such current crowding around contacts, 2 at macroscopic defects, 3 generation of defects 5 and change in alloy composition in the p-side cladding layer 7 have been proposed. Recently, we have explored a device emitting at 285 nm using scanning near field optical microscopy ͑SNOM͒ and revealed a yet another aging mechanism related to domainlike AlGaN compositional inhomogeneities in the QWs.…”
Section: Optical Studies Of Degradation Of Algan Quantum Well Based Dmentioning
confidence: 99%
“…Recent studies of UV LED degradation have identified a discrepancy between PL and EL measurements. 5,9,10 The degradation in PL (which targets the quantum wells) is either negligible or significantly less than the orders of magnitude decrease in photon counts encountered in the EL measurements. This suggests that the degradation is not occurring in the active region but more likely in the p-type cladding material increasing the number of nitrogen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple degradation mechanisms have been proposed, including device self-heating, 1 an increase in non-radiative recombination, 2 compositional inhomogeneities, 3 Al atom migration from the p-cladding layer, 4 compensation of p-type doping or generation of point defects in the cladding layer, 5,6 and current crowding around contacts 7 as well as at macroscopic defects. 8 The degradation mechanism(s) occurring in the III-nitride devices are complex and may involve point-defects, making exact identification of those mechanisms quite difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation